Beauty And The Beast (Perception Of The Phenomenon Of Beauty Privilege) - Kuswartanti, Dyah Rachman; Widhyastuti, Cahyaning; Ramadhan, Nunu (Indonesian Scientific Publication, 2024)
The phenomenon of beauty privilege where those who have beautiful faces tend to get special privileges compared to people who have ordinary faces or are even considered ugly. Beauty privilege usually provides convenience in various areas of life, such as friendship, work, and people's trust. The development of beauty privilege in society causes inequality, and so many people are affected by this phenomenon. People look more at the physical, especially an attractive physical form. Those with a beautiful physique are considered more positive, but less attractive people will be labelled worse. This study aims to determine the perception of beauty privilege in emerging adulthood. The respondents in this study amounted to 261 respondents. Data collection using a beauty privilege perception questionnaire consisting of 14 items with a validity value of 0.345-0.704 and a reliability value of 0.859. The sampling technique used is non-probability sampling with a purposive sampling type. The results of this study showed that 51.87% of respondents had a negative perception of beauty privilege, meaning that individuals think that beauty privilege is not the main thing for achieving something; individuals believe more in their abilities and inner beauty. However, the other 48.3% had a positive perception of beauty privilege, meaning that they admit that it exists around them.